2021
DOI: 10.1111/ocr.12516
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in the trabecular bone of the mandibular condyle of growing patients with sagittal jaw discrepancy treated with the twin‐block appliance

Abstract: Objective The objective of this study was to evaluate the structural changes in the trabecular bone of the mandibular condyles in patients treated with the Twin‐block functional orthopaedic appliance that act by promoting condylar growth and to compare the fractal dimension (FD) of condylar trabecular bone structure prior to treatment (T0) and after orthopaedic functional treatment (T1). Setting and sample population: This retrospective study included panoramic images of 112 individuals with a mean age of 11.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…When we compared the before and after treatment FD data in the present study, significant changes were observed in the corpus in the C‐G. Akan and Unlu Kurşun 11 performed a study in which they evaluated the trabecular structure of the mandibular condyles after twin‐block treatment, and have shown no difference in the comparison of the before and after treatment FD values in the control group. Since they investigated individuals with skeletal Class II malocclusion, it is normal that there is no significant change in condylar activity with age.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…When we compared the before and after treatment FD data in the present study, significant changes were observed in the corpus in the C‐G. Akan and Unlu Kurşun 11 performed a study in which they evaluated the trabecular structure of the mandibular condyles after twin‐block treatment, and have shown no difference in the comparison of the before and after treatment FD values in the control group. Since they investigated individuals with skeletal Class II malocclusion, it is normal that there is no significant change in condylar activity with age.…”
Section: Discussionmentioning
confidence: 67%
“…The limitation of this study was that the radiographic records used were two-dimensional. Although panoramic radiographs have proven to be reliable in FD measurements in previous studies, 10,11 further studies with three-dimensional images are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2021 , Entrenas et al, 2019 , Wishney et al, 2019 ) Antonorakis et al, claimed that by reducing overjet,the utilization of myofunctional appliances in kids having malocclusion of class II can help improve their smiles. ( Barber, 2015 , Wirawan and Herdiyati, 2018 , Akan and Kursun, 2021 ).…”
Section: Discussionmentioning
confidence: 99%